The Effect of Personality on Online Game Flow Experience and the Eye Blink Rate as an Objective Indicator - Pei-Luen Patrick Rau; Yu Chien Tseng; Xiao Dong; Caihong Jiang; Cuiling Chen (Advances in Human-Computer Interaction)
This study aimed to explore the effects of dominant and compliant personalities, on both flow experience and the external characteristics of flow experience. A total of 48 participants were recruited to play an online game and subsequently asked to recall the songs they had heard while they were playing the game. Eye blink rate was recorded. The results demonstrated that (1) the participant was immersed in the game more if he/she was relatively dominant or noncompliant; (2) the perceptions about the external environment declined remarkably while being in a flow state; and (3) eye blink rates decreased only when the flow happened at the beginning of the game, rather than throughout the whole process. The results suggested that gamers who tend to be dominant or noncompliant were more likely to experience flow. Eye blink rate and perceptions of the external environment could be objective indicators of flow experience.